Church Reform and Leadership of Change. - Askeland, Harald (Research series (Svenska kyrkan), 2015)
Reforms and processes of change have become an increasingly pervasive characteristic of European Protestant churches in the last fifteen to twenty years. Driven by perceptions of crises, such as declining membership rates, dwindling finances, decreasing participation in church rituals, and less support of traditional church doctrine, but also changes of governance of religion more generally, many churches feel compelled to explore new forms of operations, activities, and organizational structures. What is the inner dynamic and nature of these processes? This book explores this question by appl.